DIGITAL TRANSFORMATION AND BANK PERFORMANCE - Laras Pratiningsih; Nurhastuty Kesuma Wardhani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to investigate the effect of digitalization on bank profitability among Indonesian Banks. The research employs OLS on panel data of 50 banks in Indonesia during the period 2018–2022.The study reveals a positive impact of digitalization on bank profitability. The result is robust to different measures and empirical settings. Not surprisingly, small banks experience lower profitability than their peers. However, digitalization helps improve the profitability of these banks. This study explains the effect by showing that digitalization does not significantly reduce bank cost in terms of cost to income ratio and increases bank non-interest income through diversification into non-traditional products and services. In addition, the current stage of bank digitalization in Indonesia does not reduce banks’ employment costs since it requires staff to support and operate the new system. Practical implications – The research findings are motivations for bankers and policy-makers in designing appropriate strategies toward digitalization. Investors can also consider highly digitalized banks as valuable investments. This research extends the current literature on the relationship between digitalization and bank profitability, with a focus on commercial banks in Indonesia. Given the high involvement of the government and the dominance of several large banks in the banking system, the study also explores whether the effect of digitalization on bank profitability varies with the bank’s size. Last but not least, the channels in which digitalization affects bank profitability are also examined.